Elderly readmission and death after discharge from treatment of hip fracture, occurred in public hospitals from 2008 to 2010, Rio de Janeiro - Fátima de Lima Paula; Geraldo Marcelo da Cunha; Iúri da Costa Leite; Rejane Sobrino Pinheiro; Joaquim Gonçalves Valente (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
OBJECTIVES: To estimate the risk of death and readmission of a cohort of elderly patients discharged after hip fracture treatment from hospitals of the public health system; to describe the causes of these events; and to compare the rates of readmission and death observed with those of the elderly population hospitalized in public hospitals of Rio de Janeiro city. METHODS: Data on deaths and readmissions were obtained through the linkage of these two data sources: the Hospital Information System of the Sistema Único de Saúde and the Mortality Information System from the city of Rio de Janeiro. The time frame for the study was 2008 to 2011. The population consisted of 2,612 individuals aged 60 years or older with nonelective hospitalization for hip fracture who were followed for a year after discharge. RESULTS: The readmission rate in one year, excluding the deaths in this period, was 17.8%, and the death rate was 18.6%. The most common causes of death were circulatory system diseases (29.5%). Approximately 15% of the causes of readmissions were surgical complications. The state hospitals showed lower readmission risks and higher death risks compared with the federal and municipal hospitals. It was observed that there is an excess risk of readmission and hospitalization of the study population compared with the elderly population hospitalized in the public hospitals of the city. CONCLUSION: Hospitalization of elderly individuals for hip fracture causes adverse outcomes such as readmissions and deaths. Many of these outcomes can be prevented from actions recommended in the National Policy for the Elderly Health.